2002
DOI: 10.1016/s0022-1694(02)00102-6
|View full text |Cite
|
Sign up to set email alerts
|

Water table fluctuations in the riparian zone: comparative results from a pan-European experiment

Abstract: Soil saturation is known to be of crucial importance to denitrification and other nitrogen cycling processes within the riparian zone. Since denitrification potential generally increases towards the soil surface, water table elevation can control the degree to which nitrate reduction is optimised. Given their topographic location and sedimentary structure, most floodplains are characterised by high water tables. However, detailed field data on water table levels, hydraulic gradients and flow patterns within th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
131
1
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 146 publications
(139 citation statements)
references
References 23 publications
1
131
1
6
Order By: Relevance
“…The importance of riparian zone hydrology in influencing the extent of denitrification has been emphasised in many studies (e.g. Burt et al 2002;Rassam et al 2006).The classical conceptual model suggests that groundwater travels laterally and interacts with riparian sediments before discharging to the stream. This conceptual model for denitrification implies that a shallow water table intercepts the carbon-rich root zone, thus providing anoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The importance of riparian zone hydrology in influencing the extent of denitrification has been emphasised in many studies (e.g. Burt et al 2002;Rassam et al 2006).The classical conceptual model suggests that groundwater travels laterally and interacts with riparian sediments before discharging to the stream. This conceptual model for denitrification implies that a shallow water table intercepts the carbon-rich root zone, thus providing anoxic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The hydraulic conductivity of the floodplain plays a critical role. Burt et al (2002) reported that soils of medium hydraulic conductivities are most conducive to denitrification. Rassam (2005) conducted numerical modelling for coupled flow and solute transport and showed that soils with medium conductivities that range from 0.1 to 1 m day −1 are the most conducive to denitrification.…”
Section: Introductionmentioning
confidence: 99%
“…A lo largo de los márgenes del cauce de corrientes fluviales se encuentran franjas angostas de vegetación que pueden definirse como la interfase entre los ecosistemas acuáticos y terrestres (Burt et al, 2002;Granados, Hernández y López, 2006). A este tipo de comunidades vegetales que actúan como ecotonos se les conoce con el término de vegetación ribereña o riparia (Ceccon, 2003).…”
unclassified
“…Por ejemplo, estas comunidades vegetales sirven de filtro entre el río y los ambientes adyacentes, lo que impide o retarda el flujo de la escorrentía hacia el cauce, la cual en muchas ocasiones trae consigo agroquímicos, nutrientes (principalmente nitrógeno y fósforo) y productos orgánicos provenientes de las actividades antropogénicas y de los cambios en los usos del suelo (Burt et al, 2002;Carlyle y Hill, 2001;Dhondt, Boeckx, Verdehoest, Hofman y Van Cleemput, 2006;Granados et al, 2006). También, permite amortiguar los procesos de sedimentación de los lechos de los ríos y de erosión en las riberas (González y García, 1998;Pinay y Decamps, 1988;Timoney, Peterson y Wein, 1997), poseen una gran influencia sobre la calidad del agua y del ecosistema fluvial, debido a que la vegetación, principalmente la arbórea, sombrea el cauce del sistema acuático y contribuye al control del nivel de insolación y del régimen de temperaturas de las aguas; además, aumenta la cantidad de oxígeno disuelto, regula la entrada de luz al sistema y retarda el crecimiento de las algas (Ahola, 1990y Dawson y Haslam, 1983, citados por González y García, 1998Granados et al, 2006).…”
unclassified
“…Soil in riparian zones tend to have both an overall higher moisture status due to proximity to the channel and a frequent change in redox conditions as a result of seasonal changes in the water table (Burt et al 2002;. Redox sensitive elements such, As, Cr, Cu, Fe, Mn, and U, are of particular interest, as the mobility of these elements within the soil profile are linked to the redox potential of the environment (Borch et al 2010).…”
Section: Geochemistry and Implications For Sediment Fingerprintingmentioning
confidence: 99%